(untitled) (Experimental biology, 2018)
When identifying biological materials popular is the use of universal DNA-barcode. At present, the study of the genetic diversity of the flora of Northern Kazakhstan at different taxonomic levels (generic, species and subspecies) was not carried out using DNA markers. The purpose of this work was the identification and phylogenetic analysis for flora of national parks «Bayanaul» and «Burabay» by using ITS. As a source material, plant material was used, which was collected from May to July months 2015-2017 in national parks «Bayanaul» (90 species ) and «Burabay» (69 species). As a result of the research, 64 endemic and rare plant species of two national parks were visually identified. The level of genetic diversity of plants of the family Fabaceae is estimated. In phylogenetic analysis, the Lathyrus pisiformis, Trifolium repens, Medicago falcata, Oxytropis floribunda, Glycyrrhiza uralensis Fisch., the family is divided into 2 clusters of five plant genera. The intraspecific level of the genetic diversity of the Juniperus sabina L. formed two subclusters, depending on the type of population, where the Tajima index was 1.183269. The obtained data on the basis of classical approaches of taxonomy and molecular genetic methods will allow to create in the future an electronic database on endemic, rare and economically valuable plant species. Key words: Bayanaul SNNP, Burabay SNNP, flora, DNA genotyping, ITS (internal transcribed spacer)